SIFAT-SIFAT BILANGAN RAMSEY MULTIPARTIT-UKURAN UNTUK GRAF MULTIPARTIT SEIMBANG LENGKAP - Haida Fitri, Haida Fitri (LPPM Universitas Muhammadiyah Sumatera Barat, 2016)
For complete balanced multipartite graphs and , the size multipartite Ramsey number is the smallest natural number such that an arbitrary colouring of the edges of , using the two colours red and blue, necessarily forces a red or a blue as subgraph. In this paper, also discuss about the properties of size multipartite Ramsey numbers in complete balanced multipartite graphs such as, partial existence propertie, growth properties, gaps propertie and asymptotic limits propertie.Keywords: Set/ size multipartite Ramsey numbers, multipartite graph, balanced multipartite graph, complete balanced multipartite graph.